Nomad lives - Amiri, Sarieh; Audouze, Françoise; Averbouh, Aline; Bahuchet, Serge; Baroin, Catherine; Béarez, Philippe; Benjamin, Maria Helena; Berthon, Rémi; Beyries, Sylvie; Bordigoni, Marc; Bourdier, Camille; Brisebarre, Anne-Marie; et al. (Publications scientifiques du Muséum, 2022)
This book illustrates the extraordinary diversity of ‘nomad lives’ in time and space, in a tribute to Claudine Karlin, comprising 28 texts signed by economists, geographers, historians or sociologists.These case studies, organized into five chapters, are invitations to meet women, men and children from all over the world. The first chapter focuses on characterizing nomads and nomadism through examples ranging from the Aka pygmies, hunter-gatherers in the Central African forest, Yakut and Kazakh herders from the Central Asian steppes, or “nomads of contemporary globalization”. The second concentrates on the material culture of camps, from the Chatelperronians in the Grotte du Bison at Arcy-sur-Cure (Yonne) to the Manteks, Kurds in contemporary Iraq. The third examines the territories and circuits inherent to nomad lives, from the first hominids of East Africa to the break in the fishing way of life brought about by the arrival of Europeans in the Magellan Strait. Magdalenian mobility trends in the Roc-aux-Sorciers (Vienne), changes in funerary practices during the Bronze and Iron Ages in the Central Asian steppes (Kazakhstan), the sexual division of labour among the Tchouktcha of Russian Siberia, etc.: the social relations with the living and the dead, in and outside the group, are the main themes of the last two chapters.But throughout the pages a single apparently simple but extremely complex question emerges. The book ends with an attempt to answer this question from the combined perspective of an archaeologist, an ethnologist and a sociologist. Because, in the end, what does being a nomad mean? Cet ouvrage vient illustrer des fragments de vies de peuples « nomades », passés et actuels, d’Afrique, d’Asie, des Amériques du nord et du sud ou d’Europe, sous différentes facettes (habitats, productions matérielles, organisation économique et territoriale, sociale, rites et croyances, art). Ce mode de vie a prévalu pendant des millions d'années avant qu'un autre, sédentaire, ne s’y substitue progressivement à ...